An Analysis on English Learning Needs of Islamic Higher Education Students in Papua - Heni Purwati (CV. Eureka Murakabi Abadi, 2025)
This study was conducted to investigate the English learning needs for the Non-EFL students at an Islamic higher education in Papua. The analysis focused on students’ need for both general English and English for specific purposes. A descriptive qualitative research method was used in this study. The participants were the 110 non-EFL students from three faculties at IAIN Fattahul Muluk Papua. The data were collected using questionnaire and interview, with the items addressing students’ lack, wants, and necessities on English subject. The findings revealed that students considered English as an important competence and skill for their current study and future career. The survey indicated that students prefer to develop the general English competence rather than specific English. Students assessed themselves as the English beginner learners and faced difficulties to master English skills. Speaking skill seemed to be the most difficult subject, but it also became the priority skill students want to improve. In relation to students’ necessity on English subject, students prefer to engage in various English learning process and activities that are integrated to the use of technology. Learning resources that can be accessed via the internet with the digital devices and technology-based learning media are considered to be more appropriate and effective to help students improving their English competence. Overall, the results emphasize the need for English instruction that focused on general proficiency, particularly speaking skill, and incorporates technology used to better align with students’ need and learning preferences.